Meningkatkan Literasi Digital Peserta didik: Strategi Edukasi Anti-Hoaks di Media Sosial - Ainal Fitri; Futri Syam; Rizky Amalia Syahrani; Ashabul Yamin Asgha (Riau Journal of Empowerment, 2023)
The rapid development of communication technology goes hand in hand with the increase in hoax information that reaches the community, including in the environment of students. Therefore, critical thinking is needed to analyze information, namely by increasing digital literacy among students. In simple terms, digital literacy is the ability to understand and evaluate, so that the information accessed is correct and safe using digital technology. This community service aims to improve the digital literacy of students through anti-hoax strategies on social media. The community service was carried out at Madrasah Aliyah Swasta (MAS) Al-Manar on December 5, 2022, by using lecture and open discussion methods involving 40 students who were given a pre-test before the activity was carried out and a post-test after the activity. The results showed that 90% of students had received hoax news whereas during the pre-test 77.5% of students involved in this socialization activity had not been able to distinguish between hoax news and real news. However, after the digital literacy socialization activities, the post-test results showed 97.5% of students were able to distinguish hoax news on social media and were familiar with the term digital literacy.